ANALYSIS OF PROTON TRANSPORT PROPERTIES OF PSF-SPSF-TEOS BLEND MEMBRANE THROUGH POTENTIAL MEMBRANE MEASUREMENTS - APRILIA (NIM : 10508040); Pembimbing : Dr. Veinardi Suendo, NUNGKY
One of the alternative energy sources being widely developed is Polymer Electrolyte Membrane Fuel Cell (PEMFC). PEMFC is a fuel cell that uses charged polymer membrane that transports proton from anode to cathode. To produce energy, PEMFC needs oxygen from air and hydrogen as fuel to perform redox reaction and produce water. In this research, proton conducting membrane was synthesized by blending polysulfone (PSF), sulfonated polysulfone (SPSF) and tetraethoxysilane (TEOS). This membrane is expected to replace the commercial proton conducting membrane, Nafion, which is expensive and its waste is not enviromentally friendly. Here, SPSF was varied from 10 to 50 weight percent, while the total weight is kept constant. The presence of sulfonate and silanol groups in the polymer membrane is expected to increase its ability in transporting proton. Polysulfone is sulfonated with chlorosulfonic acid in chloroform where TEOS is polymerized using methanesulfonic acid as catalyst. The results of membrane potential indicate that the increase of SPSF content also increases the effective charged which means that the ability to transport proton is increased. This result is supported by proton conductivity test that also tend to increase. Supporting characterizations were also conducted such as membrane structure and morphology using Scanning Electron Microscope (SEM), Infrared (IR) spectrophotometry, and Raman spectroscopy, where the physical-chemical properties of the membrane was observed using water uptake, contact angle and ion-exchange capacity measurements.